6 - The National Produce Marketing Board in Cameroon, 1978–91: An Analysis of its Origin, Performance and Collapse - Kingsly Awang Ollong, (Afrika Zamani, 2022)
The operation of African export monopoly boards has been one of the intensively debated topics in the statutory marketing of agricultural produce. Following the reunification of the two Cameroons in October 1961, two agricultural boards were put in place to prevent the exploitation of farmers by freelance produce buyers. Against this backdrop, between 1961 and 1976, two produce boards emerged, the West Cameroon Marketing Board in West Cameroon and the Caisses de Stabilisation in East Cameroon, to control and stabilize the prices of agricultural produce. These boards merged in 1976, leading to the creation of the National Produce Marketing Board (NPMB). This article focuses on the rise, performance and collapse of the NPMB and the significance for produce marketing for the Cameroonian economy. It provides insight into the historical origins of the board, scope, activities, performance and the eventual collapse and liquidation of the National Produce Marketing Board in 1991. It highlights the fate of the coffee and cocoa sector by examining the implications of structural adjustment programmes on the activities of the National Produce Marketing Board.